Embracing complexity in landscape management: Learning and impacts of a participatory resilience assessment. Issue 1 (31st December 2022) - Malmborg, Katja; Enfors-Kautsky, Elin; Schultz, Lisen; Norström, Albert V.
ABSTRACT: Landscapes and their management are at the center of many of the sustainability challenges that we face. Landscapes can be described as social-ecological systems shaped by a myriad of human activities and biophysical processes, interacting across space and time. Managing them sustainably requires considering this complexity. Resilience thinking offers ways to address complexity in decision-making. In this paper, we analyse the learning and impact on a diverse group of local actors from participating in a participatory resilience assessment. The assessment, focused on sustainable landscape management in the Helge å catchment, Sweden, produced concrete knowledge outputs, describing ecosystem service bundles, a future vision, conceptual system models, and a strategic action plan. Follow-up interviews indicate that the process and its outputs supported the participants' learning process and helped them to articulate complexity thinking in practice. The outputs, and the exercises to produce them, emerged as complementary in supporting this articulation. Furthermore, they helped build participants' capacity to communicate the diverse values of the landscape to others and to target leverage points more strategically. Thus, it supported the application of resilience thinking in landscape management, especially by generating learning and fostering complex adaptive systems thinking.